Impacts of ammonia nitrogen on autothermal thermophilic micro-aerobic digestion for sewage sludge treatment. (December 2018) - Liu, Shugen; Yang, Xi; Yao, Xiaofei
Abstract: The concentration of ammonia nitrogen is relatively high during autothermal thermophilic micro-aerobic digestion (ATMAD), which could significantly affect the sludge stabilization. This paper aims to investigate the impacts of ammonia nitrogen on ATMAD process, batch experiments were carried out with dosage of certain amount of NH4 HCO3 into digestion system. The total ammonia nitrogen (TAN) was considered as a suitable indicator to characterize the ammonia inhibition. As the TAN reached to approximately 1000 mg L −1, the sludge digester presented a relatively low removal of volatile solids, due to adverse effects of ammonia nitrogen on sludge digestion. Three pathways that closely related to ammonia inhibition were investigated in this research. Digestion system could be inhibited by high TAN due to K + deficiency of the cells and the decline of Mg 2+ in the cytoplasm, and the accumulations of reactive oxygen species lead to oxidative stress for the microbes. Ammonia inhibition can be mitigated by the increase of oxidative enzyme. Highlights: TAN was a suitable indicator to characterize ammonia inhibition for ATMAD system. TAN adversely affected sludge digestion as it reached 1000 mg L −1 apprximately Three pathways are closely related to ammonia inhibition. High TAN resulted in the deficiencies of K + and Mg 2+ in the cells. ROS produced under micro-aerobic condition caused oxidative stress on thermophiles.